2D Ultrathin p‐type ZnTe with High Environmental Stability. (5th January 2022) - You, Shengdong; Wu, Zhen; Niu, Lijuan; Chu, Xiaohong; She, Yihong; Liu, Zhenjing; Cai, Yuting; Liu, Hongwei; Zhang, Lijie; Zhang, Kenan; Luo, Zhengtang; Huang, Shaoming
Abstract: The poor air stability hinders the practical application of most 2D materials. P‐type 2D ZnTe has drawn widespread attention, thanks to its wide direct bandgap and outstanding environmental stability. However, the controllable synthesis of ultrathin 2D ZnTe remains a huge challenge due to the intrinsic unlayered crystal structure. Here, p‐type 2D ultrathin ZnTe flakes are controllably synthesized by using space‐confined physical vapor deposition. In situ temperature‐dependent Raman and electronical measurements show the thermal stability up to 420 K and outstanding air stability even under humidity of 95%. The ZnTe flakes‐based photodetector demonstrates the broadband response varying from the visible to near infrared region, responsivity of 18.3 A W ‐1 and detectivity (D*) of 2.89 × 10 9 Jones under 405 nm illumination, implying promising potential application in electronics and optoelectronics worked in harsh environment. Abstract : The environmental sensitivity of most ultrathin 2D materials lead to rapid performance degradation when exposed to air conditions. Here, 2D p‐type ZnTe flakes were controllably synthesized by using space‐confined physical vapor deposition. In situ temperature‐dependent Raman‐photoluminescence and electronical measurements of ZnTe flakes show the outstanding environmental stability. The ZnTe photodetectors have promising potential application in extremely harsh environment.